Early Childhood Teachers’ Experiences in Integrating the Free Nutritious Meal Program into Early Childhood Learning: A Phenomenological Study - Liyana, Liyana (CV. Chandralia Bintang Pustaka, 2026)
This study aims to describe and gain an in-depth understanding of early childhood education (ECE) teachers’ experiences in integrating the Free Nutritious Meal Program into early childhood learning processes. The study employed a qualitative approach using a phenomenological method to explore the meanings and lived experiences of teachers as the primary implementers of the program at the classroom level. The research participants consisted of five kindergarten teachers in Bogor Regency, selected through purposive sampling based on the criterion of direct involvement in the implementation of the Free Nutritious Meal Program. The study was conducted from January to March 2026. Data were collected through structured interviews and analyzed using thematic analysis to identify patterns and key themes emerging from teachers’ experiences. The findings revealed four fundamental themes: the Free Nutritious Meal Program as an integrated pedagogical practice; nutritional fulfillment as a foundation for children’s learning readiness and emotional regulation; mealtime activities as a medium for character formation and social skills development; and the reflective and adaptive role of teachers in integrating policy into classroom learning practices. The findings indicate that the nutritious meal program not only impacts children’s health but also contributes significantly to the quality of learning and the holistic development of young children. This study offers a novel contribution by conceptualizing the Free Nutritious Meal Program as a holistic pedagogical practice within early childhood education and by highlighting the strategic role of teachers in bridging national policy and classroom educational practices.